Antimicrobial effect of cinnamon essential oil (Cinnamomum zeylanicum) on Salmonella strains - Montero-Recalde, Mayra (2017)
The antimicrobial effect of cinnamon essential oil (Cinnamomum zeylanicum) on strains of Salmonella choleraesuis and Salmonella typhimurium was evaluated. The cinnamon oil was obtained by the method of steam distillation, decanted, and stored at 4 °C. A completely randomized design was applied with five treatments (10, 30, 50, 70, 90% of cinnamon oil) and five replicates. The determined Minimum Inhibitory Concentration of the extract was verified at 50, 70 and 90% of the oil. On Mueller-Hinton agar, zero colony growth was observed with respect to the Minimum Bactericidal Concentration. The strain Salmonella typhimurium presented greater sensitivity to cinnamon oil than the strain Salmonella choleraesuis in relation to the diameter of the halos of sensitivity.